Expression of tandem gene fusions in transgenic tobacco plants. - Dean, C (1988)
We have studied the expression of four sets of tandem gene fusions in transgenic tobacco plants. This was to determine if the problem of between-transformant variability in expression of introduced genes could be overcome by using a linked reference gene as a co-ordinately expressed control. Tandem gene fusions containing identical 5' flanking regions (SSU301-ocs with either SSU301-cat or SSU301-SSU911) were not co-ordinately expressed in the transgenic tobacco plants whereas the tandem gene fusions containing similar but not identical 5' flanking regions (SSU301-ocs with SSU911-cat or SSU911-SSU301) were co-ordinately expressed. The lack of co-ordinate expression of some of the tandem gene fusions appears to be partially explained by absence of the corresponding genomic DNA segments in the transgenic plants.